Non-base wage components as a source of wage adaptability to shocks: Evidence from European firms, 2010-2013 - Jan Babecký; Clémence Berson; Ludmila Fadejeva; Ana Lamo; Petra Marotzke; Fernando Martins; Paweł Strzelecki (European Central Bank (ECB), 2018)
This paper provides evidence on the role of non-base wage components as a channel for firms to adjust labour costs in the event of adverse shocks. It uses data from a firm-level survey for 25 European countries that covers the period 2010-2013. We find that firms subject to nominal wage rigidities, which prevent them from adjusting base wages, are more likely to cut non-base wage components in order to adjust labour costs when needed. Firms thus use non-base wage components as a buffer to overcome base wage rigidity. We further show that while non-base wage components exhibit some degree of downward rigidity, they do so to a lesser extent than base wages.
Keywords: J30; J32; C81; P5; 330; downward nominal wage rigidity; bonuses; firm survey; European Union; Lohnrigidität; Leistungsentgelt; Arbeitskosten; Schock; EU-Staaten